A dry vibrating material for special steel smelting and preparation method thereof

By using an aluminum alloy to wrap Al2O3 and MgO in the dry vibrating material to prepare composite ball particles, the problem of short service life of aluminum-magnesium neutral dry vibrating material in the smelting environment of medium and high manganese steel is solved, and high resistance to liquid steel penetration and erosion is achieved and thermal shock resistance, extends service life and improves the compressive strength of the material.

CN118978389BActive Publication Date: 2024-12-20ZUNLONG NEW MATERIAL (SHANDONG) CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411463975.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2024-12-20
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

In the smelting environment of medium and high manganese steel, the service life of aluminum-magnesium neutral dry vibrating materials is relatively short, mainly due to the diffusion and infiltration of Mn elements in the furnace lining refractory materials, resulting in excessive damage to the material and affecting the quality of the steel.

Method used

Dry vibrating materials for special steel smelting are used, including 0.1mm < particle size ≤ 1mm, composite ball particles with 1mm < particle size ≤ 2mm, electromelted white corundum, 97 electromelted magnesium sand, high-purity sintered magnesium sand , magnesium aluminum spinel micropowder and TiO2 micropowder, and composite ball particles are prepared by a mixture of Al2O3 and MgO by aluminum alloy, thereby improving the material's resistance to liquid steel penetration and corrosion resistance.

Benefits of technology

It significantly improves the anti-porous penetration and corrosion performance of dry vibrating materials and extends the service life, and the detection line change rate after insulation at 1600℃ is low, the pressure resistance is high, and the liquid steel does not contaminate.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention provides a dry vibratory material for special steel smelting and its preparation method, belonging to the field of refractory materials technology. The dry vibratory material, by weight, comprises the following raw material components: 9-11 parts of composite spherical particles with a particle size of 0.1mm < ≤ 1mm, 9-11 parts of composite spherical particles with a particle size of 1mm < ≤ 2mm, 67-68 parts of fused white corundum, 4.8-5.2 parts of 97% fused magnesia, 2.5-2.9 parts of high-purity sintered magnesia, 4.3-4.7 parts of magnesium aluminum spinel micro powder, and 0.28-0.32 parts of TiO2 micro powder. The dry vibratory material for special steel smelting prepared by this invention is boron-free, exhibits excellent resistance to steel molten penetration and erosion, has good thermal shock resistance, a long service life, and does not contaminate the steel molten material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dry vibrating material for special steel smelting and a preparation method thereof, belonging to the technical field of refractory materials. Background Art

[0002] With the development of metallurgical industry technology, coreless medium frequency induction furnaces (50~1000Hz) are currently widely used in non-ferrous metal smelting, steelmaking, casting and other industries due to their advantages of energy saving, high efficiency, flexible operation, fast heating, low pollution, easy atmosphere control, and intermittent operation. As an important part of the induction furnace, the performance and service life of the lining refractory are of vital importance to steel smelting. Dry vibrating materials for lining refractory materials are mainly divided into three categories according to their chemical properties: acidic, neutral, and alkaline. Aluminum-magnesium neutral dry vibrating materials have the characteristics of high mechanical strength, thermal shock resistance, high temperature volume stability, excellent corrosion and penetration resistance, and environmental friendliness. They are currently widely used in the steel and iron smelting industry.

[0003] At present, a certain amount of Mn element needs to be added to high-quality special steel, which can not only deoxidize and reduce sulfur, improve the strength and hardness of steel, and improve the cold brittleness performance, but also improve the steel's wear resistance, toughness, weldability and corrosion resistance. Therefore, in steel production, especially in steel used in marine engineering, energy and chemical industry, medium and high manganese steel with added Mn element has been widely used.

[0004] However, under the smelting environment of medium and high manganese steel, the service life of the furnace lining refractory materials mainly composed of aluminum-magnesium neutral dry vibrating materials is greatly reduced. This is mainly reflected in the strong diffusion and penetration ability of the Mn element in the molten steel into the furnace lining refractory materials, and it is oxidized to MnO at the interface between the steel and the furnace lining refractory materials, which reacts with the main component of the furnace lining refractory Al. 2 O 3 A large amount of liquid phase will be formed. At the same time, MnO can also react with non-main components (CaO, SiO 2 The low melting point is formed, which causes the furnace lining material to be damaged too quickly and seriously affects the quality of the steel. Summary of the invention

[0005] In view of the shortcomings of the prior art, the present invention provides a dry vibrating material for special steel smelting and a preparation method thereof, to achieve the following invention objectives: when the dry vibrating material is used as a refractory material for furnace lining for special steel smelting, it has good resistance to steel liquid penetration and erosion, good thermal shock resistance and long service life.

[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0007] A dry vibrating material for special steel smelting, the dry vibrating material, in parts by weight, comprises the following raw material components: 9-11 parts of composite ball particles with a particle size of 0.1 mm < ≤ 1 mm, 9-11 parts of composite ball particles with a particle size of 1 mm < ≤ 2 mm, 67-68 parts of fused white corundum, 4.8-5.2 parts of 97 fused magnesia, 2.5-2.9 parts of high-purity sintered magnesia, 4.3-4.7 parts of magnesia-alumina spinel powder, TiO 2 Micro powder 0.28-0.32 parts.

[0008] The preparation method of the composite ball particles is:

[0009] The Al-Mg-Si alloy is heated to a molten state, and then cooled to 590-610° C. to reach a semi-solid state, thereby obtaining a semi-solid molten alloy;

[0010] Al 2 O 3 The micro powder and the MgO micro powder are uniformly mixed to obtain an inorganic mixture, and then the inorganic mixture is preheated to 253-257° C. and maintained for 28-32 minutes to obtain a preheated inorganic mixture powder;

[0011] The preheated inorganic mixture powder is added to the semi-solid molten alloy, mixed and stirred for 590-610 seconds to obtain a molten composite slurry, and then the molten composite slurry is heated to 768-772°C, kept at a constant temperature, stirred for 8-12 minutes, and then cooled and processed into composite ball particles.

[0012] In the Al-Mg-Si alloy, Al≥98wt%, Mg: 0.4-0.6wt%, Si: 0.4-0.6wt%, Fe≤0.2wt%; 2 O 3 Micro powder D 50 2.8-3.2 μm; D 50 5.9-6.1μm.

[0013] The Al 2 O 3 The mass ratio of the micropowder to the MgO micropowder is 7:2.8-3.2; the weight ratio of the preheated inorganic mixture powder to the semi-solid molten alloy is 1:8.8-9.2.

[0014] In the fused white corundum, the mass ratio of fused white corundum with a particle size of 0.5 mm ≤ < 8 mm, fused white corundum with a particle size of 0.088 mm ≤ < 0.5 mm, and fused white corundum with a particle size of < 0.088 mm is 51: (4.9-5.1): (11.4-11.6).

[0015] In the 97 fused magnesia, the mass ratio of 97 fused magnesia with a particle size of 0.088 mm ≤ <1 mm to 97 fused magnesia with a particle size of <0.088 mm is 3: (1.8-2.2);

[0016] In the high-purity sintered magnesia sand, the mass ratio of the high-purity sintered magnesia sand with a particle size of 0.088 mm ≤ <1 mm to the high-purity sintered magnesia sand with a particle size of <0.088 mm is 1: (1.6-1.8).

[0017] The particle size of the magnesium aluminum spinel powder is less than 0.045 mm; the magnesium aluminum spinel powder is fused magnesium aluminum spinel powder, and the aluminum oxide content is 75-77wt%; the TiO 2 The particle size of the micro powder is less than 0.045 mm.

[0018] The fused white corundum has an aluminum oxide content of ≥99.5wt%; the high-purity sintered magnesia has a magnesium oxide content of ≥98.0wt% and a silicon oxide content of ≤0.3wt%.

[0019] The preparation method of the dry vibration material comprises mixing composite ball particles with a particle size of 0.1 mm < ≤ 1 mm with TiO 2 The micro powder is premixed evenly first, and then composite ball particles with a particle size of 1mm<≤2mm, fused white corundum, 97 fused magnesia, high-purity sintered magnesia, and magnesia-alumina spinel micro powder are added and mixed evenly to obtain dry vibration material for special steel smelting.

[0020] Compared with the prior art, the present invention achieves the following beneficial effects:

[0021] (1) The dry vibrating material for special steel smelting prepared by the present invention is free of boronization, has excellent resistance to penetration and erosion of molten steel, good thermal shock resistance, long service life, and no pollution to molten steel.

[0022] (2) After the dry vibration material prepared by the present invention is formed and kept at 1600°C for 3 hours, the test line change rate is 4%, the compressive strength is 15MPa, and the volume density is 2.72g / cm 3 .

[0023] (3) The dry vibrating material prepared by the present invention is used as a furnace lining refractory material and is formed and applied to the furnace lining of an induction furnace. Medium and high manganese steel is added to the induction furnace. After being kept at 1600°C for 90 minutes, the erosion thickness of the furnace lining refractory material is 0.3 mm, and the penetration thickness is 0.5 mm. After being kept at 1600°C for 150 minutes, the erosion thickness of the furnace lining refractory material is 0.45 mm, and the penetration thickness is 0.70 mm. DETAILED DESCRIPTION

[0024] Example 1

[0025] Step 1: heating the Al-Mg-Si alloy (Al≥98wt%, Mg: 0.5wt%, Si: 0.5wt%, Fe≤0.2wt%) in an electric melting furnace to about 765°C to be molten, and then cooling to about 600°C to reach a semi-solid state to obtain a semi-solid molten alloy;

[0026] Al 2 O 3 Micro powder (D 50 =3μm) and MgO powder (D 50 = 6μm) and mixed evenly with alumina ceramic ball mill (Al 2 O 3 The mass ratio of micropowder and MgO micropowder is 7:3) to obtain an inorganic mixture, and then the inorganic mixture is preheated to about 255°C and maintained for 30 minutes to remove moisture to obtain a preheated inorganic mixture powder to enhance the wettability between the inorganic substance and the molten alloy liquid, and also help to improve the dispersion uniformity of the inorganic substance in the molten alloy.

[0027] Step 2: Add the preheated inorganic mixture powder to the semi-solid molten alloy (the weight ratio of the preheated inorganic mixture powder to the semi-solid molten alloy is 1:9), mix and stir for 600 seconds to obtain a molten composite slurry, and then heat the molten composite slurry to 770°C, maintain a constant temperature, and use 400rpm electric stirring for 10 minutes, then pour the molten mixture into a sand mold to cool, and finally machine it into a spherical composite material, referred to as composite spherical particles, the particle sizes of the composite spherical particles are: 0.1mm<particle size ≤1mm, 1mm<particle size ≤2mm.

[0028] Step 3: Mix the composite sphere particles with a particle size of 0.1 mm < ≤ 1 mm and TiO 2 The micro powder is premixed evenly first, and then composite ball particles with a particle size of 1mm<≤2mm, fused white corundum, 97 fused magnesia, high-purity sintered magnesia, and magnesia-alumina spinel micro powder are added and mixed evenly to obtain dry vibration material for special steel smelting.

[0029] The dry vibrating material for special steel smelting comprises the following raw material components in parts by weight:

[0030] 10 parts of composite ball particles with a particle size of 0.1mm<≤1mm, 10 parts of composite ball particles with a particle size of 1mm<≤2mm, 67.5 parts of fused white corundum, 5 parts of 97 fused magnesia, 2.7 parts of high-purity sintered magnesia, 4.5 parts of magnesia-alumina spinel powder, TiO 2 0.3 parts of micro powder.

[0031] In the fused white corundum, the mass ratio of fused white corundum with a particle size of 0.5 mm ≤ < 8 mm, fused white corundum with a particle size of 0.088 mm ≤ < 0.5 mm, and fused white corundum with a particle size of < 0.088 mm is 51:5:11.5;

[0032] The fused white corundum has an alumina content of ≥ 99.5wt%;

[0033] In the 97 fused magnesia, the mass ratio of 97 fused magnesia with a particle size of 0.088 mm ≤ <1 mm to 97 fused magnesia with a particle size of <0.088 mm is 3:2;

[0034] In the high-purity sintered magnesia, the mass ratio of high-purity sintered magnesia with a particle size of 0.088 mm ≤ <1 mm to high-purity sintered magnesia with a particle size of <0.088 mm is 1:1.7;

[0035] The high-purity sintered magnesia has a magnesium oxide content of ≥98.0wt% and a silicon oxide content of ≤0.3wt%.

[0036] The particle size of the magnesium aluminum spinel powder is less than 0.045 mm;

[0037] The magnesium aluminum spinel powder is fused magnesium aluminum spinel powder, and the aluminum oxide content is 76wt%;

[0038] The TiO 2 The particle size of micro powder is less than 0.045mm;

[0039] The composite spherical particles of 0.1 mm < particle size ≤ 1 mm and TiO 2 Premix the micro powder evenly to strengthen the TiO 2 Dispersed burning effect.

[0040] After the dry vibration material prepared in Example 1 was formed and kept at 1600°C for 3 hours, the test line change rate was 4%, the compressive strength was 15MPa, and the volume density was 2.72g / cm 3 .

[0041] The dry vibrating material prepared in Example 1 is used as a refractory material for the lining of a 20 kg induction furnace. Medium and high manganese steel is added to the induction furnace. After insulation at 1600°C for 90 minutes, the erosion thickness of the refractory material for the lining is 0.3 mm, and the penetration thickness is 0.5 mm. After insulation at 1600°C for 150 minutes, the erosion thickness of the refractory material for the lining is 0.45 mm, and the penetration is 0.70 mm.

[0042] The medium-high manganese steel includes the following components: C content is 0.4wt%, Mn content is 10wt%, Al content is 2wt%, and Sn content is 0.005wt%.

[0043] Comparative Example 1

[0044] Based on Example 1, the changes are: Al-Mg-Si alloy is not used to coat Al 2 O 3 Micropowder and MgO micropowder, Al-Mg-Si alloy is melted to prepare alloy particles with a particle size of 0.1 mm < ≤ 1 mm and alloy particles with a particle size of 1 mm < ≤ 2 mm; Al-Mg-Si alloy and Al 2 O 3 The amounts of micropowder and MgO micropowder are the same as those in Example 1. The specific feeding method in the third step is modified to add alloy particles with a particle size of 0.1 mm < ≤ 1 mm and TiO 2 The micro powder is premixed evenly, and then alloy particles with a particle size of 1mm<≤2mm, Al 2 O 3 Micro powder, MgO micro powder, fused white corundum, 97 fused magnesia, high purity sintered magnesia and magnesia-aluminum spinel micro powder are mixed evenly to obtain dry vibration material for special steel smelting.

[0045] After the dry vibration material prepared in Comparative Example 1 was formed and kept at 1600℃ for 3h, the test line change rate was 6.5%, the compressive strength was 10.5MPa, and the volume density was 2.67g / cm 3 .

[0046] The dry vibrating material prepared in Comparative Example 1 was used as a furnace lining refractory material in the lining of a 20 kg induction furnace. Medium and high manganese steel was added to the induction furnace. After being kept at 1600°C for 90 minutes, the erosion thickness of the furnace lining refractory material was 0.8 mm and the penetration thickness was 1.2 mm.

[0047] The composition of the medium-high manganese steel is the same as that of Example 1.

[0048] The results of comparative example 1 show that: Al-Mg-Si alloy is not used to coat Al 2 O 3 Micro powder and MgO micro powder are just Al-Mg-Si alloy made into alloy particles, and then Al-Mg-Si alloy particles, Al 2 O 3 The dry vibrating material prepared by mixing micropowder, MgO micropowder separately with other raw material components has a significantly improved linear change rate after being kept at 1600°C for 3 hours, and a significantly reduced compressive strength. When applied to furnace lining refractory materials, the erosion thickness is 2.67 times that of Example 1, and the penetration thickness is 2.4 times that of Example 1.

[0049] Comparative Example 2

[0050] Based on Example 1, the changes are: omitting TiO 2 By adding micro powder, dry vibration material is prepared.

[0051] After the dry vibration material prepared in Comparative Example 2 was formed and kept at 1600℃ for 3h, the test line change rate was 4.1%, the compressive strength was 11.2MPa, and the volume density was 2.62g / cm 3 .

[0052] The dry vibrating material prepared in Comparative Example 2 was used as a furnace lining refractory material in the lining of a 20 kg induction furnace. Medium and high manganese steel was added to the induction furnace. After being kept at 1600°C for 90 minutes, the erosion thickness of the furnace lining refractory material was 0.7 mm and the penetration thickness was 1.0 mm.

[0053] The composition of the medium-high manganese steel is the same as that of Example 1.

[0054] The results of Comparative Example 2 show that: omitting TiO 2 After adding the micropowder, a dry vibrating material was prepared. The compressive strength was significantly reduced after being kept at 1600°C for 3 hours. When applied to furnace lining refractory materials, the erosion thickness was 2.33 times that of Example 1, and the penetration thickness was 2 times that of Example 1.

[0055] In the prior art, if metallic aluminum is added to dry vibrating materials, due to the small amount added and the large density difference with the non-metallic mineral raw materials, the metallic aluminum will be unevenly dispersed and most of it will be segregated in some large holes, making it difficult to resist the penetration of molten steel and strengthen the material structure.

[0056] The present invention adopts aluminum alloy to wrap Al 2 O 3 A mixture of aluminum and MgO is prepared to obtain composite ball particles with graded aluminum alloy uniformly wrapped with composite oxides, which has a small density difference from other raw material components of dry vibration materials, and the composite ball particles can be well and evenly distributed in the dry vibration material.

[0057] When dry vibrating materials are used for furnace lining refractory materials, during the high temperature process of use, the metal plastic phase (Al-Mg-Si alloy) effectively improves the strength and thermal shock resistance of the furnace lining refractory materials and promotes the sintering of the materials. The alumina and magnesium oxide react evenly and gradually expand, which can effectively resist the defects and damage caused by sintering shrinkage. At the same time, the metal is squeezed and plasticized to strengthen the bonding between the particle interfaces, thereby improving the erosion and penetration resistance of the furnace lining refractory materials.

[0058] At the same time, the metal aluminum can prevent the rapid oxidation and reaction of manganese in the molten steel to form a low-melting phase at the interface. After the metal aluminum itself is oxidized, it reacts with the added TiO 2 Micro powder reacts to generate Al 2 TiO 5 (Alumina and titanium oxide can react to form Al 2 TiO 5), it can prevent the generation and expansion of cracks and improve the strength and service life of the furnace lining refractory materials.

[0059] Part Ti 4+ (Derived from TiO 2 ) is solid-dissolved in magnesia-alumina spinel, causing spinel lattice distortion and reducing sintering activation energy, thereby further improving the anti-penetration and anti-erosion properties of the furnace lining refractory materials.

Claims

1. A dry vibrating material for special steel smelting, characterized by: The dry vibration material comprises the following raw material components in parts by weight: 9-11 parts of composite ball particles with a particle size of 0.1 mm < ≤ 1 mm, 9-11 parts of composite ball particles with a particle size of 1 mm < ≤ 2 mm, 67-68 parts of fused white corundum, 4.8-5.2 parts of 97 fused magnesia sand, 2.5-2.9 parts of high-purity sintered magnesia sand, 4.3-4.7 parts of magnesium aluminum spinel powder, and 0.28-0.32 parts of TiO2 powder; the composite ball particles are prepared by coating semi-solid molten alloy Al-Mg-Si with evenly mixed Al2O3 powder and MgO powder.

2. The dry vibrating material for special steel smelting according to claim 1, characterized in that: The preparation method of the composite ball particles is: The Al-Mg-Si alloy is heated to a molten state, and then cooled to 590-610° C. to reach a semi-solid state, thereby obtaining a semi-solid molten alloy; The Al2O3 powder and the MgO powder are uniformly mixed to obtain an inorganic mixture, and then the inorganic mixture is preheated to 253-257° C. and maintained for 28-32 minutes to obtain a preheated inorganic mixture powder; The preheated inorganic mixture powder is added to the semi-solid molten alloy, mixed and stirred for 590-610 seconds to obtain a molten composite slurry, and then the molten composite slurry is heated to 768-772°C, kept at a constant temperature, stirred for 8-12 minutes, and then cooled and processed into composite ball particles.

3. The dry vibrating material for special steel smelting according to claim 2, characterized in that: In the Al-Mg-Si alloy, Al≥98wt%, Mg: 0.4-0.6wt%, Si: 0.4-0.6wt%, Fe≤0.2wt%; the Al2O3 powder D 50 2.8-3.2 μm; D 50 5.9-6.1μm.

4. The dry vibrating material for special steel smelting according to claim 2, characterized in that: The mass ratio of the Al2O3 powder to the MgO powder is 7:2.8-3.2; the weight ratio of the preheated inorganic mixture powder to the semi-solid molten alloy is 1:8.8-9.

2.

5. The dry vibrating material for special steel smelting according to claim 1, characterized in that: In the fused white corundum, the mass ratio of fused white corundum with a particle size of 0.5 mm ≤ < 8 mm, fused white corundum with a particle size of 0.088 mm ≤ < 0.5 mm, and fused white corundum with a particle size of < 0.088 mm is 51: (4.9-5.1): (11.4-11.6).

6. The dry vibrating material for special steel smelting according to claim 1, characterized in that: In the 97 fused magnesia sand, the mass ratio of 97 fused magnesia sand with a particle size of 0.088 mm ≤ <1 mm and 97 fused magnesia sand with a particle size of <0.088 mm is 3: (1.8-2.2); in the high-purity sintered magnesia sand, the mass ratio of high-purity sintered magnesia sand with a particle size of 0.088 mm ≤ <1 mm and high-purity sintered magnesia sand with a particle size of <0.088 mm is 1: (1.6-1.8).

7. The dry vibrating material for special steel smelting according to claim 1, characterized in that: The particle size of the magnesium aluminum spinel powder is less than 0.045 mm; the magnesium aluminum spinel powder is fused magnesium aluminum spinel powder with an aluminum oxide content of 75-77 wt %; the particle size of the TiO2 powder is less than 0.045 mm.

8. The dry vibrating material for special steel smelting according to claim 1, characterized in that: The fused white corundum has an aluminum oxide content of ≥99.5wt%; the high-purity sintered magnesia has a magnesium oxide content of ≥98.0wt% and a silicon oxide content of ≤0.3wt%.

9. The method for preparing the dry vibrating material according to any one of claims 1 to 8, characterized in that: The composite ball particles with a particle size of 0.1 mm < ≤ 1 mm and TiO2 powder are premixed evenly, and then the composite ball particles with a particle size of 1 mm < ≤ 2 mm, fused white corundum, 97 fused magnesia, high-purity sintered magnesia, and magnesia-aluminum spinel powder are added and mixed evenly to obtain dry vibration material for special steel smelting.